A retrospective analysis of the prognostic implications of glycemic variability on all-cause mortality in critically ill patients with mitral valve disease - Jie Peng; Xingzhan Zhang; Yunjing Mai; Hongzhi Chen; Dakai Liang; Shaobo Li; Huanhuan Wu; Chao Li; YuanShuo Ge; Guangdong Wang; Ling Zhao (Frontiers in Endocrinology)
BackgroundMitral valve disease is associated with higher cardiovascular morbidity and mortality. Glycemic variability (GV), reflecting blood glucose fluctuations, acts as an independent indicator for results in critically ill patients. However, it’s effect on patients in the ICU with mitral valve disease is unclear.MethodsAll blood glucose measurements of patients with mitral valve disease were extracted from MIMIC-IV database. GV was assessed using the coefficient of variation of glucose levels. Cox hazard regression models and restrictive cubic spline (RCS) were applied to examine the link between GV and outcomes. A threshold effect analysis was also conducted to explore potential inflection points. Subgroup analyses were performed to assess consistency across demographics and clinical subgroups.ResultsThe study of 3,378 adults with mitral valve disease found that higher GV was significantly associated with increased 28-day and 90-day mortality, as shown by Cox regression analysis. Subgroup analyses confirmed these findings.ConclusionsFor ICU patients with mitral valve disease, elevated GV was an independent predictor of short-term mortality. GV was recommended for consideration in risk stratification and glucose management strategies, particularly in non-diabetic critically ill populations. Monitoring and targeting GV were proposed to new avenues for improving clinical outcomes in this high-risk group.